The Effect of Government Macroeconomic Policy on Indonesia's Fisheries Export to The United States in 1989-2019 - Firmansyah, Tanto; Jayadi, Akhmad (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2021)
Indonesia is a maritime country that has huge potential in fisheries sector. The average of indonesian fisheries production and export volumes always increase every year. This study aims to analyze the effect of exchange rates, government spending, inflation, interest rates, and sanitation policies to Indonesia fishery export to the United States in 1989-2019. Data were obtained from the Indonesian Ministry of Finance, the World Bank, UN COMTRADE, and the Indonesian Ministry of Maritime Affairs and Fisheries. This study uses the Error Coerrection Model (ECM) method to examine the effect of the independent variables on the dependent variable in the long term and short term. This study explains that in the long-term, government spending and exchange rate have positive effect, and interest rates have negative effect on export. In short-term, government spending and exchange rate have positive effect on export. Inflation and sanitation policy do not affect export in the long-term or short-term, while interest rates in the short-term do not affect Indonesian fishery exports. Keywords: Exports, Government Spending, Exchange Rates, Non-Tariff Barriers, Error Correction Model. JEL: F10, F13, C32